A GIMMICK FOR MIMIC: THE ELT STUDENT-TEACHERS' ATTITUDES TOWARDS DRAMA COURSE - Nurdan Kavaklı (Informascope, 2016)
As a part of interaction-based meaningful activities, the use of drama techniques in education has gained popularity so far. The purpose of this study is to tackle the question whether the drama course together with the in-class applications contribute to the attitudes of prospective English language teachers. In that, the study is composed of the quantitative analysis of the attitudes of the prospective teachers from third graders at English Language Teaching (hereafter ELT) department. The data is gathered through the use of a 25-question-attitude scale (Topoğlu & Erden, 2012) which has been administered to all participants, in sum composed of 37 sophomore students. The results have indicated positive attitudes towards drama course held in ELT department within the scope of desire to increase in course duration, continuity of the course for future benefits, the development of personal, interactional and social skills, and the improvement of the creativity skill.